Infiltration controls in a tallgrass prairie at a hillslope scale - Auvenshine, Sarah D. (Kansas State University, 2011)
Infiltration capacity influences the ability of a soil to absorb and transmit water through macropores and micropores of the soil structure. Infiltration is primarily influenced by the soil type, which is dependent on a number of factors including parent material, climate, biological activity, and topography. Spatial controls of land use, land cover, soil texture, slope position, slope gradient and slope aspect are a few of the variables influencing infiltration capacity within a uniform soil type. The goals of the thesis are to (1) quantify the spatial distribution of soil hydraulic properties at the surface of a hillslope using one measurement method - the automated mini-disk tension infiltrometer - and several analysis methods, (2) determine the dependence of depth on soil hydraulic properties using two measurement methods, and (3) compare the results of the investigation with information from the soil survey and soil investigations. First, automated mini-disk infiltrometers were used to determine soil hydraulic properties at ten sites along a hillslope in Konza Prairie Natural Research Area. Several analysis methods were used to extract hydraulic conductivity and sorptivity values from the infiltration data. Next, large intact soil cores were extracted from three selected sites at the same hillslope and analyzed at six depths using a large disk infiltrometer. Finally, the six segments of the large soil cores were analyzed using the same methods as the field measurements with the mini-disk infiltrometers. The results of the field investigation at the ten sites show a variability of soil hydraulic properties over an assumed homogeneous landscape. The values of hydraulic conductivity and sorptivity are dependent on the method of analysis. An empirically based approach produced more realistic values than a physically based approach. The results of the laboratory investigation of the three extracted soil cores also show a dependence of method of analysis and measurement. In addition, the results show a complex relationship among landscape position, depth, and soil structure. Finally, while soil surveys and soil descriptions can provide detailed information on soil properties, an infiltration investigation at a detailed spatial scale provides quantitative values for soil hydraulic properties.
Keywords: Konza Prairie; Hydrology; Infiltration; Hydraulic conductivity; Civil Engineering (0543)